Disciplinary Differences and University Teachers’ Perspectives: Possibilities of Applying the Teaching Perspectives Inventory - Jovana Milutinović; Biljana Lungulov; Aleksandra Anđelković (Center for Educational Policy Studies Journal)
Based on the conceptual and empirical framework of five perspectives on teaching and earlier studies that have suggested a link between teaching perspectives and teachers’ academic disciplines, this paper aimed to examine the differences in the university teachers’ perspectives from various academic disciplines and faculties. This research also aimed to validate the Teaching Perspectives Inventory on a sample of 526 university teachers in Serbia. The results confirmed the differences in the university teachers’ perspectives and led to the conclusion that hard sciences teachers were more teacher-centred, while soft sciences teachers were more student-centred. Additionally, exploratory factor analysis indicated that the slightly modified version of the TPI is applicable and reliable to use in other educational contexts. However, it can be concluded that research on teachers’ perspectives is limited to specific cultural, educational, and research contexts.